CHARACTERISTICS OF SMALL INTESTINE BIOCENOSIS AND THE IMPACT OF DISORDERS ON FUNCTIONAL DYSPEPSIA - Yarova, J.S.; Kharchenko, N.V.; Kharchenko, V.V. (World of Medicine and Biology, 2025)
The purpose of the study to determine the prevalence of small intestinal bacterial overgrowth by conducting a lactulose breath test in patients with functional dyspepsia, to evaluate differences in clinical course of functional dyspepsia. To study the effectiveness of standard therapy (pantoprazole) and an approach with small intestinal bacterial overgrowth eradication (pantoprazole and rifaximin). Small intestinal bacterial overgrowth prevalence in the group with functional dyspepsia was significantly higher (p